Aplicação e avanços da espectroscopia de luminescência em análises farmacêuticas - Sotomayor, Maria Del Pilar Taboada [UNESP]; Dias, Iara Lúcia T.; Lanza, Marcos R. V.; Moreira, Altair Benedito [UNESP]; Kubota, Lauro T. (Sociedade Brasileira de Química, 2008)
This paper provides a review on the latest advances and applications of the luminescence spectroscopy for the development of pharmaceuticals analyses methods, basically based on the photo- and chemiluminescence. The different forms of the drugs determination on pharmaceuticals through the fluorescence and chemiluminescence are discussed. The analyses include the drugs native fluorescence (liquid and solid-phases); the fluorescence from the oxidizing or reducing forms of the drug; the fluorescence from the chemical derivatization and their photochemistry and hydrolysis reactions. The quenching of luminescence and chemiluminescence generation for the pharmaceutical quantification are also shown. Finally, the trends and future perspectives of the luminescence spectroscopy in the field of the pharmaceutical research are discussed.
Application and advances in the luminescence spectroscopy in pharmaceutical analyses
Keywords: luminescence spectroscopy; drugs; cosmetics analysis